Cost-effectiveness of rhythm control strategy: Ablation versus antiarrhythmic drugs for treating atrial fibrillation in Korea based on real-world data - Kim, Woojin; Kim, Min; Kim, Yun Tae; Park, Woongbi; Kim, Jin-bae; Kim, Changsoo; Joung, Boyoung (Frontiers in Cardiovascular Medicine, 2023)
Background Ablation-based treatment has emerged as an alternative rhythm control strategy for symptomatic atrial fibrillation (AF). Recent studies have demonstrated the cost-effectiveness of ablation compared with medical therapy in various circumstances. We assessed the economic comparison between ablation and medical therapy based on a nationwide real-world population. Methods and findings For 192,345 patients with new-onset AF (age ≥ 18 years) identified between August 2015 and July 2018 from the Korean Health Insurance Review and Assessment Service (HIRA) database, medical resource use data were collected to compare AF patients that underwent ablation (N = 2,131) and those administered antiarrhythmic drugs (N = 8,048). Subsequently, a Markov chain Monte Carlo model was built. The patients had at least one risk factor for stroke, and the base-case used a 20-year time horizon, discounting at 4.5% annually. Transition probabilities and costs were estimated using the present data, and utilities were derived from literature review. The costs were converted to US $ (2019). Sensitivity analyses were performed using probabilistic and deterministic methods. The net costs and quality-adjusted life years (QALY) for antiarrhythmic drugs and ablation treatments were $37,421 and 8.8 QALYs and $39,820 and 9.3 QALYs, respectively. Compared with antiarrhythmic drugs, incremental cost-effectiveness ratio of ablation was $4,739/QALY, which is lower than the willingness-to-pay (WTP) threshold of $32,000/QALY. Conclusion In symptomatic AF patients with a stroke risk under the age of 75 years, ablation-based rhythm control is potentially a more economically attractive option compared with antiarrhythmic drug-based rhythm control in Korea.